PENGARUH METODE PELATIHAN TERHADAP KETERAMPILAN JURUS TUNGGAL PENCAK SILAT PADA ATLET PEMULA (10-12 TAHUN) DI PERGURUAN BAKTI NEGARA KECAMATAN TEGALLALANG GIANYAR - Ni Luh Putu Spyanawati; Ni Wayan Mudariani (Lambung Mangkurat University, 2015)
The Effect Of The Whole Training Method And Half Training Method Toward The Skill Of A Single Empthy - Handed Pencak Silat To Beginner Athletes (10-12 Years Old) In Bakti Negara Institution Tegallalang Subdistrict, Gianyar Regency. The research aim is to know the whole and half training method toward single stance empty handed Pencak silat. The subjects of study are beginner athlete (10 – 12 years old) male from Bakti Negara instituation, subdistrict of Tegallalang, Gianyar Regency which are consist of 30 people. The research design of this study is experimental research which is consists of the modified group pre-test – post-test design. The data collection is consists of single stance empty handed instrument skill pencak silat. The data analysis is using (t-test) with 5% significance and supported by SPSS computer program16.0 with 0.05 significances.The result of data analysis (1) whole training method influenced to single stance empty handed pencak silat skill, with its result thit = 14,10 >ttab = 2,048, (2) half training method method influenced to single stance empty handed pencak silat skill, with its result thit = 7,20 >ttab = 2,048, (3) there are differences inskill single stance empty handed pencak silat between whole and partial training methods, seen from the data gain score with the results significance thit=11.086and the significance of the count was 0,000 smaller than α (0.000 <0.05) means that the whole training method and half training method have differences. The whole training method give better effect than half training method toward single stance empty handed pencak silat to beginner athletes(10-12 years old), it can be seen from the average of the data gain score whole training method=8.57>half training method=4.77.It can be concluded that (1) there is the effect of the whole training method to single stance empty handed skill for pencak silat in beginner athletes (10-12 years old), (2) there are significant whole training method to single stance empty handed skill for pencak silat in beginner athletes (10-12 years old), (3) there are differences in skill acquisition single stance empty handed skill pencak silat between the whole training method and in half training method, where the whole training method is better than the half of training methods to single stance empty handed skill for pencak silat in beginner athletes (10-12 years old). Keywords: methods, training, single stance skill, beginner athletes